2022
DOI: 10.1111/age.13200
|View full text |Cite
|
Sign up to set email alerts
|

A genetic investigation of equine recurrent uveitis in the Icelandic horse breed

Abstract: Summary Equine recurrent uveitis (ERU) is an autoimmune disease defined by inflammation of the uveal tract of the eye. The cause of ERU is thought to be complex, involving both genetic and environmental factors. The purpose of this study was to investigate potential genetic risk factors for ERU in the Icelandic horse. Fifty‐six Icelandic horses (11 affected with ERU and 45 controls) living in Denmark and the USA, eight years or older, were included in the study. A case–control GWAS was performed using the GGP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additional investigations are needed to determine the relative risk of these two classifications of ERU among Icelandic horses. A genome‐wide association study using the same population of Icelandic horses identified an association on ECA 11, but no causal genetic risk factors have been identified at this time 107 . Additional investigations are needed to replicate these findings and identify potential variants for further investigations to understand the role of genetics in the onset of ERU among Icelandic horses.…”
Section: Genetic Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additional investigations are needed to determine the relative risk of these two classifications of ERU among Icelandic horses. A genome‐wide association study using the same population of Icelandic horses identified an association on ECA 11, but no causal genetic risk factors have been identified at this time 107 . Additional investigations are needed to replicate these findings and identify potential variants for further investigations to understand the role of genetics in the onset of ERU among Icelandic horses.…”
Section: Genetic Risk Factorsmentioning
confidence: 98%
“…Breed predisposition provides evidence of a genetic component for the development of ERU. For example, classic ERU has been recognized to occur more commonly among warmblood and Icelandic horses, although limited information about prevalence of the classic subtype is available for these breeds 9,107 . For posterior ERU, previous investigations identified an overrepresentation of warmblood horses among ERU cases, but limited information is available about the propensity or relative risk for developing posterior uveitis for any one breed 4,7 …”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…The inciting causes for development of ERU are likely multifactorial and remain unclear in many cases, but may involve genetic predisposition in certain breeds (e.g., Appaloosas, Warmbloods, Icelandics) or infection with Leptospira spp. (5, [9][10][11][12]. Current treatments for ERU include a combination of topical and systemic anti-inflammatories, atropine, antibiotics (if active Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%